Application of response surface methodology in describing fusion characteristics of rigid poly(vinyl chloride)/nanoclay/wood flour/calcium carbonate hybrid nanocomposites. Issue 3 (4th July 2014) - Saeb, M.R.; Moghri, M.
<x xml:space="preserve">Abstract</x> The fusion characteristics of poly(vinyl chloride) hybrid nanocomposites containing different amounts of nanocalcium carbonate, wood flour, and nanoclay fillers were investigated utilizing response surface methodology (RSM). Various nanocomposites were prepared through a two‐step mixing process, wherein the minimum and maximum torque values, the fusion time, and fusion factor were monitored through torque‐time plastograms provided during melt processing. A quadratic model was developed by using RSM to probe the individual and interactive effects of nanoclay, nanocalcium carbonate, and wood flour on the fusion parameters. Optimized formulations with enhanced fusion properties were achieved by using contour plots of RSM. J. VINYL ADDIT. TECHNOL. 21:183–190, 2015. © 2014 Society of Plastics Engineers